Correlation of blood gas status with the mortality of neonates admitted in ICU (Northern International Medical College Journal, 2018)
Background : Blood gas abnormalities are frequently encountered in sick neonates admitted in ICU. They contribute significantly to mortality. Therefore, blood gas status is a helpful indicator of the condition of sick neonate.Objective : To study the correlation between blood gas status and mortality of neonates admitted in ICU.Methods : This observational study was carried out at the ICU of Dhaka Shishu Hospital (DSH) from January 2014 to July 2014. Total 121 neonates were enrolled according to inclusion criteria and analyzed their blood gas status which were correlated with the mortality of neonates.Results : Perinatal asphyxia (PNA) was common disorder with the highest mortality in neonate followed by sepsis and pneumonia. Significant association between mortality with lower pH, PC02 and higher base excess was observed. Metabolic acidosis was the most common acid-base disorder.Conclusion : Low pH, PC02 and more base excess are predictor of mortality in this group of neonate. Initial acid-base derangement significantly correlates with the mortality of critically ill neonates requiring ICU care.Northern International Medical College Journal Vol.9(1) July 2017: 261-263